PENGARUH PROGRAM TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PT INDUSTRI KERETA API (PERSERO) TERHADAP KINERJA KEUANGAN PADA UMKM DI MADIUN RAYA - Fatya Athallah Dhisa Ramadhiarto; Yuli Tri Cahyono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
MSMEs are one of the supporters of sustainable national economic growth, but in reality, there are still many obstacles faced by MSME actors in increasing business profitability. The TJSL program is one of the BUMN programs that can help MSMEs. This study aims to examine the effect of the social and environmental responsibility program of PT Industri Kereta Api (Persero) on the financial performance of MSMEs in Madiun Raya. The sampling technique used total sampling obtained by 41 MSMEs. The method of data analysis in this study used multiple linear regression analysis with SPSS version 25. The results showed that capital soft loans and assistance/grants affected the financial performance of MSMEs, while the application of training and coaching did not affect the financial performance of MSMEs.